2014
DOI: 10.3109/17453674.2014.972262
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for postoperative urinary retention in fast-track hip and knee arthroplasty

Abstract: Background and purpose Postoperative urinary retention (POUR) is a clinical challenge, but there is no scientific evidence for treatment principles. We describe the incidence of and predictive factors for POUR in fast-track total hip (THA) and knee arthroplasty (TKA).Patients and methods This was a prospective observational study involving 1,062 elective fast-track THAs or TKAs, which were performed in 4 orthopedics departments between April and November 2013. Primary outcome was the incidence of POUR, defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 15 publications
3
53
0
Order By: Relevance
“…A recent prospective cohort study in THA also demonstrated continued unspecified analgesic use in 32% of patients, as well as a median pain level of 4/10 6 months after surgery (von Dincklage et al., ). However, their patients all had general total intravenous anaesthesia, whereas the use of neuraxial anaesthesia has been reported in about 90% of procedures in the departments contributing to our cohort (Bjerregaard et al., ).…”
Section: Discussionmentioning
confidence: 84%
“…A recent prospective cohort study in THA also demonstrated continued unspecified analgesic use in 32% of patients, as well as a median pain level of 4/10 6 months after surgery (von Dincklage et al., ). However, their patients all had general total intravenous anaesthesia, whereas the use of neuraxial anaesthesia has been reported in about 90% of procedures in the departments contributing to our cohort (Bjerregaard et al., ).…”
Section: Discussionmentioning
confidence: 84%
“…Post-operative urinary retention was found in 40% of THA and TKA patients by Bjerregaard et al, 36 especially in males with pre-operative voiding problems, and patients with spinal analgesia had increased risk. Intermittent catheterisation should be used instead of permanent catheterisation with a safety limit of 800 cc before catheterisation.…”
Section: Peri-operative Optimisationmentioning
confidence: 93%
“…According to Bjerregaard et al, [19] the incidence of post-arthroplasty urinary retention was 40%, and their risk was increased when using spinal anesthesia, without relevant influence with age, gender and type of arthroplasty. The application of spinal anesthesia is a risk factor for urinary retention, increasing the postoperative catheterization by about 50% when compared to general anesthesia [19].…”
Section: Discussionmentioning
confidence: 99%
“…According to Bjerregaard et al, [19] the incidence of post-arthroplasty urinary retention was 40%, and their risk was increased when using spinal anesthesia, without relevant influence with age, gender and type of arthroplasty. The application of spinal anesthesia is a risk factor for urinary retention, increasing the postoperative catheterization by about 50% when compared to general anesthesia [19]. On the other hand, Griesdale et al, [20] in their cohort study on urinary retention after hip and knee arthroplasty, demonstrated the incidence of 43.3% of urinary retention in the first 24 hours postoperatively, assuming that being men that underwent hip arthroplasty and used morphine as associated risk factors; The risk of urinary retention among men was 60.4%, compared with 28.5% among women; And, compared to general anesthesia, men who perform spinal anesthesia with morphine have a 7.1 up to 12.2 times greater chance of urinary retention [20].…”
Section: Discussionmentioning
confidence: 99%